Changes of Jute Seed Qualities Under Ambient Storage Condition - Alam, ATMM; Haque, MM; Rasul, MG; Khan, MAA; Karim, MA (Annals of Bangladesh Agriculture, 2022)
Experiment was conducted to determine the changes of jute seed qualities under ambient storage condition over one year period. Jute seed produced from three genotypes (O-72, O-3820 and Acc.4311) sown on three dates (31 July, 15 August and 30 August) over four locations (Manikganj, Cumilla, Dinajpur and Jashore) and preserved in plastic containers at ambient condition. Seed qualities were assessed in the laboratory for every six months of storage. Results showed that fresh jute seed maintained 94 to 98% germination which declined with the advent of storage period. Irrespective of genotype, sowing date and location, germination capacity of jute seed remained more than 80% up to 6 months of storage at ambient condition. Afterwards, seed harvested from genotype Acc.4311 sown on 15 August at Manikganj maintained the highest germination (86%) after 12 months of storage. Seedling dry weight of all the genotypes also decreased over the storage period. However, rate of reduction of seedling dry weight was lower in seed harvested from the crop sown on 15 August which indicates that seed obtained from this time can maintain better seedling dry weight even after 12 months of storage. Contrary, electrical conductivity of seed electrolytes increased with the increase of storage period although it was the lowest (285 μ Scm-1) in seed of genotype Acc.4311 harvested from 15 August sowing at Manikganj. Considering different qualities of stored jute seed, the genotype Acc.4311 supposed to be promising for producing good quality seed sown on mid-August at Manikganj environment. Ann. Bangladesh Agric. (2021) 25 (1) : 79-87